Implementasi Program Puspaga Dalam Pemberdayaan Masyarakat Wilayah RW 06 Kelurahan Sidodadi Kecamatan Simokerto Kota Surabaya - Elisa Salsabilla; Eddy Wahyudi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Child abuse is a serious issue that requires serious attention. In Surabaya City, the implementation of the PUSPAGA Program (Family Learning Center) is an effort to prevent child abuse. This program has clear objectives and is supported by competent human resources. Although the program has been running, there are challenges in reaching all target groups and responding to changes in the community. This research uses the Policy Implementation theory by Merilee S. Grindle to analyze the program's implementation. The results of the research indicate that the content of the PUSPAGA Program policy has been well explained, but it is not fully understood by the target groups. The human resources involved in the program are already competent, but there are challenges in responding to changes in the community. Thus, the PUSPAGA program in Surabaya City has the potential to enhance community empowerment in the prevention of child abuse. However, further efforts are needed to ensure that all target groups understand and support the program, as well as to improve responsiveness to changes in the community.